Determinants of market value of goats in Afghanistan - TAVVA, SRINIVAS; AW-HASSAN, ADEN; RIZVI, JAVED; SAHARAWAT, YASHPAL SINGH (The Indian Journal of Animal Sciences, 2016)
An attempt was made to identify factors influencing goat production and marketing which is at subsistence level in crop-livestock production system and to scale it up to commercial level in Nangarhar and Baghlan provinces of Afghanistan. Data were collected from 240 goat producers that were randomly selected in equal proportions for rainfed and irrigated systems from 24 villages in 4 districts of target provinces. Results from the double-log linear regression model used for both meat and dairy goats indicated that age of goat and production system were significantly influencing meat goats while in case of dairy goats, these factors were non-significant but positive. However, some common determinants were live weight of goat, place of marketing, source of market information and location of goat producers. The study enables goat producers to plan their goat sales with higher incomes and reinforce their motivation to scale up production.